2015
DOI: 10.1177/1941874415588749
|View full text |Cite
|
Sign up to set email alerts
|

Full Implementation of Screening for Nutritional Risk and Dysphagia in an Acute Stroke Unit

Abstract: Background and Purpose: In patients with acute stroke, undernutrition and aspiration pneumonia are associated with increased mortality and length of hospital stay. Formal screening for nutritional risk and dysphagia helps to ensure optimal nutritional management in all patients with stroke and to reduce the risk of aspiration in patients with dysphagia. We developed a national guideline for nutritional and dysphagia screening in acute stroke, which was introduced in our stroke unit on June 1, 2012. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
9
0
2
Order By: Relevance
“…This may have contributed to the low dysphagia rate. Similar to our study, Kampman et al [19] reported 23% of patients to fail an initial swallowing screening test in an unselected stroke patient sample. Arnold and colleagues diagnosed dysphagia in 20.7% of 570 consecutive patients treated in a tertiary stroke center [1].…”
Section: Discussionsupporting
confidence: 79%
“…This may have contributed to the low dysphagia rate. Similar to our study, Kampman et al [19] reported 23% of patients to fail an initial swallowing screening test in an unselected stroke patient sample. Arnold and colleagues diagnosed dysphagia in 20.7% of 570 consecutive patients treated in a tertiary stroke center [1].…”
Section: Discussionsupporting
confidence: 79%
“…Two studies did not report ages, but specified the population as adult or geriatrics. The majority of studies included participants with stroke ( n = 19) [ 34 36 , 38 , 39 , 42 , 48 , 51 54 , 56 60 , 62 , 66 , 68 ]. Fifteen studies included patients with diverse diagnoses: e.g., post-surgery, internal medicine, geriatrics, pneumonia, trauma, gastrointestinal tract disease, cardiovascular disease, respiratory tract disorders, fractures, musculoskeletal, neurologic and neurodegenerative diseases, and head and neck cancer [ 25 , 27 , 28 , 33 , 40 , 43 , 45 , 47 , 50 , 55 , 61 , 63 , 69 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over half (26/44) of studies reported OD prevalence data using screening and clinical non-instrumental assessments methods or tools that were either designed by the authors for the purpose of the study or modified versions of published tools, thus lacking information on diagnostic performance and psychometric properties [ 26 28 , 34 , 36 , 38 – 42 , 44 46 , 48 , 52 54 , 58 60 , 62 , 64 66 , 70 , 72 ]. Of the screening and clinical non-instrumental assessment tools used to determine OD with known diagnostic performance and psychometric properties, the Volume-Viscosity Swallow Test (V-VST) [ 74 ] was the most commonly used screen [ 47 , 55 , 61 , 63 , 64 , 68 ] and the Eating Assessment Tool-10 (EAT-10) [ 75 ] was the most frequently used PROM [ 33 , 37 , 43 , 47 , 49 , 50 , 69 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…O estudo destes casos permitiu ajuizar sobre a importância da avaliação sistemática da deglutição e o acompanhamento do risco nutricional dos doentes com AVC que exigem um esforço contínuo (25) .…”
Section: Os Doentes Demonstraram De Uma Forma Geral Deter Conheciment...unclassified